SPERM MORPHOLOGY STUDY BY CONVENTIONAL SEMEN ANALYSIS METHOD IN KHYBER PAKHTUNKHWA POPULATION - Khan, Muhammad Jaseem; Muhammad, Anees; Khan, Malik Zeb; Haroon, Mohammad (Annals of Allied Health Sciences, 2019)
OBJECTIVE: To determined the frequency of various infertile male population by conventional method. METHODS: Conventional semen analysis method was used according to the world health organization guidelines. Statistical Package for social sciences version 21.0 was used for statistical analysis. RESULTS: Out of 1103 specimen, 88 (7.97%) were azoospermic, 108 (9.79%) were oligozoospermic and 406 (36.8%) were asthenozoospermic. CONCLUSION: Comparatively the azoospermic population was decreased approximately 50% with reference to the previous studies, oligozoospermia was slightly decreased and asthenozoospermia was slightly increased. New technique for the measurements of sperm motility should be accurate and more precise. Need a molecular study regarding the infertility level of male population.